Flow cytometric characterisation of acute leukaemia in adolescent and adult Ethiopians - Jemal Alemu; Balako Gumi; Aster Tsegaye; Abdulaziz Sherif; Fisihatsion Tadesse; Amha Gebremedhin; Rawleigh Howe (African Journal of Laboratory Medicine)
Background: Flow cytometric characterisation of acute leukaemia is a key diagnostic approach for clinical management of patients, but is minimally practised in resource-constrained settings like Ethiopia.